Journey of Rural Woman Empowered Through Educational Struggles to Become a University Teacher - Adhikari, Surya Prasad; Upadhya, Shanta (SNPRC Journal, 2024)
This study explores the lived experiences of a Brahmin woman from rural western Nepal to understand how gender norms, sociocultural ideologies, and familial structures have shaped her educational and professional trajectory. Using a qualitative life history research design, the study focuses on an in-depth narrative of a woman (pseudonym: Nandi) who was married at a young age and confronted various socio-cultural expectations that confined her to traditional domestic roles. Despite these constraints, Nandi’s journey demonstrates how personal agency, coupled with familial support especially from her father and later her husband created pathways for educational empowerment. The study employs thematic analysis grounded in feminist and sociocultural perspectives to unpack how gender ideologies and rural power structures were negotiated at the household level. Findings of this study reveal that emotional support from family members, flexible educational arrangements, and institutional access played pivotal roles in enabling her to pursue higher education after marriage and childbirth. Nandi’s story illustrates the transformative power of education in redefining a woman's identity beyond conventional gender roles and highlights the importance of intra-family dynamics in facilitating or hindering women's empowerment. Her narrative underscores that while patriarchal structures persist, they are neither monolithic nor unchangeable; rather, they can be re-negotiated through relational agency and strategic family alliances. The study concludes that in order to promote gender equity in rural Nepal, educational policies must account for socio-cultural realities and emphasize community engagement, family support mechanisms, and institutional flexibility to support women's lifelong learning and empowerment.